2017
DOI: 10.1164/rccm.201611-2265oc
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Airflow Limitation Based on z-Score Underestimates Mortality in Patients with Chronic Obstructive Pulmonary Disease

Abstract: In patients with COPD, the AL classification based on z-score predicts worse mortality than those based on percentage of predicted. It is possible that the z-score underestimates AL severity in patients older than 60 years of age with severe functional impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…Similar to our study, other studies have found that decreased ppFEV 1 , FEV 1 z‐score or FEV 1 Q are associated with an increased risk of death . Furthermore, a study by Mannino et al .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similar to our study, other studies have found that decreased ppFEV 1 , FEV 1 z‐score or FEV 1 Q are associated with an increased risk of death . Furthermore, a study by Mannino et al .…”
Section: Discussionsupporting
confidence: 92%
“…Similar to our study, other studies have found that decreased ppFEV 1 , FEV 1 z-score or FEV 1 Q are associated with an increased risk of death. 6,14,30,31 Furthermore, a study by Mannino et al 32 found that the risk of death increased with worsening GOLD-defined airflow limitation, where participants with severe or very severe obstruction were associated with 4.5 times higher risk of dying compared to participants with normal lung function. HR were slightly higher than in our study, likely due to the exclusion of participants with respiratory symptoms from their reference population.…”
Section: Discussionmentioning
confidence: 99%
“…To estimate the implied impact on LE, we used a parametric survival function which was estimated using the functional form (Weibull, Gompertz or exponential) that minimized the Akaike information criteria (AIC). 26,27 The remaining LE were extrapolated using the estimated model taking into account the already known diagnoses of COPD, asthma and CVD at baseline and presented graphically as the remaining LE compared to the LE of a never smoker with no respiratory symptoms. CI for LE and years of life lost (YLL) were derived by bootstrapping (sampling with replacement) and used the 2.5 and 97.5 centiles from 2000 LE estimate repetitions.…”
Section: Discussionmentioning
confidence: 99%
“…While the ATS/ERS classification is based on the FEV 1 expressed in percentage of the predicted value (%pred) [1], the GLI new classification is based on the FEV 1 Z -scores [3]. This could be a source of confusion [6,8]. …”
mentioning
confidence: 99%
“…This study finding do not support the above conclusions. In the cohort study of Tejero et al [8] ( n  = 2614 patients with chronic obstructive pulmonary disease (COPD)), based on ATS/ERS [1] and GLI [11] classifications, 33.2% and 35.7% had mild, 39.9% and 36.2% had moderate, 18.5% and 20.9% had severe, and 8.3% and 7.3% had very severe OVD. Like in this study, in the aforementioned one [8], the classification based on Z -score [3] showed little concordance with the ATS/ERS classification [1]: according to the Z -score classification [3], 66.3% of COPD remained with the same severity, while 23.7% worsened and 10.0% improved.…”
mentioning
confidence: 99%